Treatment application of rivaroxaban in Chinese patients with livedoid vasculopathy - Chen, Wenji (J Pain Res, 2017)
Livedoid vasculopathy (LV) is a chronic prothrombotic disease of cutaneous micro-circulation resulting in cutaneous ischemia and infarction. As a rare disease, LV has an estimated incidence of ten cases per million. Not only correct diagnosis but also effective treatments are very difficult for patients with LV. Due to the lack of large-scale studies in this rare disease, LV poses a great challenge to the doctors, and existing treatment has always been an individual attempt with off-label application. The main goals in the treatment of patients with LV are to avoid the repeated occurrence of active cutaneous lesions and prevent painful ulceration and irreversible scarring. The current report describes the cases of three Chinese patients with LV receiving rivaroxaban treatment, an oral direct inhibitor of factor Xa inhibitor, and observes the treatment effect of rivaroxaban during the follow-up. As an injection-free alternative to low-molecular-weight heparin (LMWP) and monitoring-free alternative to warfarin, rivaroxaban improves the quality of life and enhances the compliance of patients. All patients consider rivaroxaban as more tolerable than previous drugs and, therefore, continue the application of rivaroxaban, effectively improving the treatment effect of drugs and successfully avoiding the repeated occurrence of active cutaneous lesions. Treatment application of rivaroxaban in Chinese patients with LV successfully avoids the recurrence of active cutaneous lesions and prevents the progressive ulceration and scarring.